Actualization of the QMS documents of the independent agency of personnel certification; Ресурсосберегающие технологии в контроле, управлении качеством и безопасности - Buyankina V. I. Vladislava Igorevna; Galtseva (Gal’tseva) O. V. Olga Valerievna; Goncharov D. V. Dmitry Vladimirovich; Sarsikeev Yermek Zhaslanovich Y. Zh. Yermek Zhaslanovich (2025, 2025)
Quality management systems (QMS) are becoming one of the key factors contributing to the successful operation of enterprises in a rapidly changing market economy, constantly increasing competitive pressure and increased consumer demands on the quality of products. Actualization of the QMS documents is an integral part of confident and strategic management of any organization, ensuring not only compliance with standards, but also continuous improvement of processes, which in turn allows achieving sustainability and growth. Quality management systems cover a wide range of processes and documents, including quality policy, management processes, instructions and standards governing the activities of employees. Actualization of these documents is necessary to reflect the current state of affairs in the organization, changes in legislation, new requirements from consumers and technological progress. These processes contribute not only to improving the efficiency of the enterprise, but also to ensuring its adaptability to changes in the external environment